Interorganisational systems within SMEs aggregations: an exploratory study on information requirements of an industrial district. (19th September 2011) - Pigni, Federico; Ravarini, Aurelio; Buonanno, Giacomo; Sciuto, Donatella
Even though companies have become efficient in managing information and logistics inside their boundaries, communication and coordination among partner, within an InterOrganisational Information System (IOS), is far from effective. In a global market where the success of a company relies on its entire supply chain, design and implementation of an IOS are mandatory. Small and Medium-sized Enterprises (SMEs), and in particular those inside Industrial Aggregations (IAs), could greatly benefit from IOS implementation, but a widely accepted model of IOS adoption is missing. This paper proposes a framework to analyse the relationships among the main players of IAs and presents its application to an industrial district.